Solid Dispersions Prepared by Continuous Cogrinding in an Air Jet Mill. Issue 11 (16th September 2013) - Muehlenfeld, Christian; Kann, Birthe; Windbergs, Maike; Thommes, Markus
<x xml:space="preserve">Abstract</x> Embedding a poorly water‐soluble drug as a solid dispersion in a hydrophilic carrier by cogrinding is a possible strategy for enhancing the drug dissolution rate. Although general interest in continuous processes for manufacturing drug formulations has increased, many publications still focus on batch processes. The jet mill used in this study is a promising tool for continuous cogrinding. Investigation of different drug‐to‐carrier ratios (griseofulvin/mannitol) demonstrated that a drug load of 10% is best suited to investigate the enhanced dissolution behavior. To gain deeper insight into the underlying mechanisms, the coground dispersion is compared with different physical mixtures in terms of physicochemical properties and dissolution behavior. Differential scanning calorimetry and X‐ray powder diffraction were used to verify the crystalline structure of the coground formulation. On the basis of the Hixson–Crowell model, particle size reduction was ruled out as the main reason for dissolution enhancement. An increase of surface free energies because of grinding is shown with contact angle measurements. Confocal Raman microscopy investigations revealed the drug's bulk dispersity in the coground formulation as an additional factor for the increased dissolution rate. In conclusion, the continuous cogrinding approach is a promising technique to prepare the drug in a rapidly dissolving, yet crystalline, form. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:4132–4139, 2013